Getting to Sweden, Part I: War and Malfeasance, 1720–1850. (15th March 2015) - Teorell, Jan; Rothstein, Bo
<x xml:space="preserve">Abstract</x> How and why some countries were able to make the historical transition from a patrimonial, nepotistic and corrupt bureaucracy to a clean, Weberian and professionalised one is still an under‐studied topic in the literature on corruption. This article presents original data on such a transition in the case of Sweden, drawing on court hearings of cases of malfeasance among public officials in the period 1720–1850. It is argued, theoretically, that an important explanation for why the Swedish bureaucracy was able to break out of the collective action trap of corruption relates to Charles Tilly's theory of the importance of war for state‐making. Rather than viewing war‐making in itself as a driver of change, however, this article pinpoints the importance of having lost a significant war – in the Swedish case, the war against Russia in 1808–9 – and the constitutional and regime changes this set in motion. Drawing on comparative data on malfeasance, the similarities in this regard between the Swedish and Danish cases are highlighted.